Analysis of Multimedia Physics Learning in Integrated Package Learning Tools on Senior High School - Muhammad Sahal; Muhammad Nasir (Universitas Riau, 2020)
Abstract. Use of multimedia Learning physics is a must for a physics teacher so that learning can take place well . This research aims to develop and analysis of multimedia physics learning integrated with packing preparation of learning tools in senior high school by using adobe animate application. This research method used is Research and Development (R & D) with ADDIE’s model. Method steps include analysis, design, development, implementation and evaluation and then empirical analysis with use it in limited class. The instrument of learning device validity developed consisted of aspect of planning, pedagogic, content and technique. The result of multimedia validation in aspect of planning got the average mark was 0.91 with high category, aspect of pedagogic is 0.94 with high category, aspect of content is 0.96 with high category and aspect of technique is 0.90 with high category empirical analysis show that α = 0.82 so multimedia in this research was declared valid and reliable to use as physics learning media for senior high school